(untitled) (Revista Peruana de Investigación Educativa, 2014)
While inequalities related to technology access and use are increasingly the focus of educational policy and practice, educators and policymakers alike continue to struggle to define and conceptualize the notion of a «digital divide». This divide could be conceived as a lack of access to technology and as a problem solved by simply providing Internet and computer access. As basic technology access has increased, attention has instead shifted to disparities in the broad array of factors that allow technologies to be effectively used. Rather than a technocentric framework that sees technology access alone as the solution to inequality, this paper draws from critical conceptualizations of print literacy in order to reframe the digital divide in terms of social inclusion through technology. The paper first provides examples of attempts to bridge the digital divide in India, Ireland, Egypt, and Peru. Based on these examples and other research, the paper then describes a framework for using technology for social inclusion. This framework aims to reorient the discussion of the digital divide toward one that includes the physical, digital, human, and social resources that facilitate meaningful digital access and use by all.